Friday

December 19, 2014

December 19, 2014

Posted by **Tony** on Tuesday, March 20, 2007 at 9:39am.

2x+3y=1

5x+3y=16

Subtract the first equation from the second. (Subtract left and right sides separately). This gives you

3x = 15

Then divide both sides by 3.

x = 5

Pretty easy, huh?

After you have x, you can get y by using any of the original equations.

10 + 3y = 1

Subtract 10 from both sides.

3y = -9

Divide both sides by 3

y = -3

2x + 3y =1

5x + 3y = 16

Multiply the 2nd equation by -1, then add them together like this:

2x + 3y = 1

-5x - 3y =-16

_________________

-3x = -15

Divide by -3 to get x =5. Now, substitute 5 for x in one of the equations and solve for y.

**Answer this Question**

**Related Questions**

Algebra - I am re posting this for fear that it was overlooked earlier. I have ...

math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...

math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...

math - My problem I have involves a method that requires using the quadratic ...

Math - I am really have a tough time trying to solve this problem. I think my ...

math,help!!!! - How do i do thois problem?Please help. Problem #1 solve the ...

chemestry - Balance th following equation in acid Solutiong and determind if it...

proof by mathematical induction - subject is PreCalulus. 2^(k+3) = and < (k+3...

ALGEBRA - Select all the statements that can be used as steps to solve the ...

Algebra - Select all the statements that can be used as steps to solve the ...